An Interpretation of the Fundamental Concepts of Law Enforcement in the Hungarian Legal System - Buzás, Gábor (Magyar Rendészet, 2016)
Is there any reason to use the phrase “order protection” (rendvédelem) instead or beside law enforcement (rendészet) in Hungarian? What does it really mean? My personal opinion is: it is unnecessary and disturbing. In the second part of my paper I am examining the correlation — as the legal basis of the police action — between the scope of authority and power of authority. In the third part of my paper I will write about the differences and content of the public safety and public order.